Eating contexts and their associations with socio-demographic factors in Brazilian adolescents (EVA-JF Study) - Felipe Silva Neves; Vanessa Sequeira Fontes; Mário Círio Nogueira; Priscila Moreira de Lima Pereira; Eliane Rodrigues de Faria; Michele Pereira Netto; Renata Maria Souza Oliveira; Ana Paula Carlos Cândido (Cambridge University Press, 2023)
Abstract Objective: To describe the eating contexts and estimate their associations with socio-demographic factors in a sample of Brazilian adolescents. Design: Cross-sectional study. We used an exploratory questionnaire about eating contexts (encompassing regularity of meals, places where they occur and if they take place with attention and in company), which was submitted to cluster analysis. Subsequently, three clusters were identified: cluster 1, 'appropriate eating contexts at breakfast, lunch and dinner'; cluster 2, 'inappropriate eating context at breakfast' and cluster 3, 'inappropriate eating context at dinner'. Multinomial logistic regression models were performed, without and with adjustments, using cluster 1 as reference. Setting: Twenty-nine public schools of Juiz de Fora, MG, Southeast Brazil. Participants: Adolescents, 14-19-year-olds (n 835). Results: We observed relevant prevalence of adolescents omitting breakfast (52·9 %) and dinner (39·3 %), and who had the habit of eating sitting/lying on the couch/bed or standing/walking, and in front of screens. Breakfast usually occurred unaccompanied (70·8 %); around half (47·5 %) and little over a third (36·1 %) of the sample also would usually have lunch and dinner unaccompanied, respectively. Furthermore, through multivariate analysis, we found associations of eating contexts clusters with female sex (more likely in clusters 2 and 3), age range 14-15-year-olds (less likely in cluster 2) and higher mother's schooling (more likely in cluster 3). Conclusions: We verified an alarming prevalence of adolescents with eating contexts unaligned with healthy eating recommendations. Additionally, inappropriate eating contexts at breakfast and/or at dinner were associated with socio-demographic factors (sex, age range and mother's schooling).